2004
DOI: 10.1086/383573
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Severe Impact of Lipodystrophy on the Quality of Life of Patients Infected with HIV-1

Abstract: A standardized questionnaire was used to assess the impact of lipodystrophy (LD) on quality of life (QoL). Eighty-four consecutive asymptomatic human immunodeficiency virus type 1 (HIV-1)-infected outpatients with clinical LD completed a modified version of the Dermatology Life Quality Index (DLQI) survey to measure the impact of body fat changes on their QoL. Body changes influenced dressing for 55 patients (65%), produced feelings of shame for 41 (49%), and disrupted sexual life for 23 (27%). There was a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 8 publications
2
47
0
7
Order By: Relevance
“…Even though the sample size was small, men scored lower on negative mood and homosexual men scored lower on psychological functioning. On a subsample of this study 8 applying a different questionnaire, Blanch and coauthors 9 found that changes in the breast, face, or legs were significantly associated with greater impairment of psychosocial functioning. In the multivariate analysis only changes in the breast remained significant.…”
Section: Lipodystrophy and Quality Of Life 581mentioning
confidence: 83%
See 1 more Smart Citation
“…Even though the sample size was small, men scored lower on negative mood and homosexual men scored lower on psychological functioning. On a subsample of this study 8 applying a different questionnaire, Blanch and coauthors 9 found that changes in the breast, face, or legs were significantly associated with greater impairment of psychosocial functioning. In the multivariate analysis only changes in the breast remained significant.…”
Section: Lipodystrophy and Quality Of Life 581mentioning
confidence: 83%
“…6,7 Few studies have addressed quality-of-life issues in HIVinfected patients with LD, and its impact has not been es-tablished definitively. Some studies demonstrating effects have used instruments not widely validated in people with HIV infection, 8,9 while others have failed to find correlations with health-related quality of life. 10,11 The main objective of this study was to identify the impact of LD on the health-related quality of life in HIV-infected people taking HAART.…”
mentioning
confidence: 99%
“…However, as QoL for HIV+ patients during HAART may change due to the positive effects of HAART counterbalanced by the effects of BFR [4], we included an extra domain containing five facets specific for HIV+ patients receiving HAART. These items were generated from preliminary subjects' interviews, opinions of clinicians and social scientists working in the field of HIV/AIDS and a literature search [6,9,23]. These facets included feeling ashamed in public, problems of dressing style and clothes' size, feeling less confident about one's health, fear of HIV status being revealed by changes in body-fat distribution and being embarrassed due to body-fat changes.…”
Section: Quality-of-life Assessmentsmentioning
confidence: 99%
“…The effects of BFR abnormalities on patients' QoL [8,9], the aetiology and prevalence of BFR [2,3,10] and strategies to manage metabolic disorders associated with BFR [11 12] have all been previously studied. However, there remains a paucity of information on the effects of interventions such as exercise training (EXS) on QoL in HAART-treated HIV+ patients with BFR in sub-Saharan Africa where the prevalence of HIV is highest in the world and access to HIV treatment is improving.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the association between individual ARV drugs and body fat changes is important, because these fat changes can be stigmatizing, particularly when involving fat loss in the face 12,13 and have been associated with decreased quality of life 14 and decreased ARV adherence. 15 Treatment options including antiretroviral switch strategies as well as surgical implants and injectables to correct fat loss are being explored.…”
Section: Introductionmentioning
confidence: 99%